The 8-year incidence of obesity and type 2 diabetes in five African-origin populations - Conradie, Catharina Beatrix (Department of Public Health and Family Medicine, 2025)
Obesity and type 2 diabetes (T2D) have become worldwide pandemics, particularly in low middle-income countries and among African-origin populations. The Modeling of Epidemiological Transition Study (METS, 2009) enrolled 2,506 African-origin participants, aged 25-45, from five countries and its ancillary study; METS-Microbiome, continued yearly research visits in 2,085 participants (2018-2019). The countries represent the full epidemiological transition spectrum, represented by the Human Development Index: Ghana (low), South Africa and Jamaica, (middle), Seychelles (high) and the United States (US) (very high). Research visits included anthropometrics, body composition measurements, social history, socio-demographics and health questionnaires, physical activity by accelerometer and clinical measurements. Overall, 732 participants had complete measurements from both METS (baseline) and METS-Microbiome (follow-up). At baseline, the US participants had the highest obesity prevalence (61.0%) and Ghanaians the lowest (11.5%). However, the obesity prevalence increased significantly, most notably among the Ghanaians (125%; p<0.001), and Seychellois (60.7%; p<0.01). Significant obesity predictors included being females, waist circumference and fat mass (p<0.001). The interaction term for follow-up length and site was significant with higher odds of obesity compared to baseline; Ghana (OR 6.62, 95%CI 1.56-28.35), Jamaica (OR 4.57, 95%CI 1.06-8.88) and Seychelles (OR 4.31, 95%CI 1.12-16.57). The US participants had the highest T2D prevalence (10,0%) and Jamaicans (0%) at baseline. However, the Seychellois experienced a 600% increase in T2D prevalence (p<0.01) accompanied by the highest T2D and obesity incidence rate. The interaction term for follow up length and site was similarly significant with higher odds of T2D at follow-up; Seychellois (OR 10.00, 95%CI 1.83-54.52) and US (OR 2.33, 95%CI 1.17-4.66). Age (p=0.002) and waist circumference (p=0.016) were significant T2D predictors. In conclusion, the study underscores significant increases in obesity and T2D rates, not only in high-income countries but also in rapid transitioning settings, highlighting concerns about healthcare resources readiness for the growing global burden of non-communicable diseases.